Differential expression of the TRAIL/TRAIL-receptor system in patients with inflammatory bowel disease - Brost, Sylvia; Koschny, Ronald; Sykora, Jaromir; Stremmel, Wolfgang; Lasitschka, Felix; Walczak, Henning; Ganten, Tom M. (Pathology, research and practice, 2010)
TNF-related apoptosis inducing-ligand (TRAIL) is a potent inducer of apoptosis and plays an important role in immune regulation. To explore the role of TRAIL in inflammatory bowel disease (IBD), we examined the expression of the TRAIL/TRAIL-receptor system in colonic resections from patients with ulcerative colitis and Crohn's disease in comparison to normal colon and appendicitis. TRAIL and TRAIL-receptor (TRAIL-R) expression was assessed in resections of normal colon, colon of IBD patients, and appendicitis by immunohistochemistry. TRAIL was downregulated in enterocytes of patients with IBD, but was upregulated in mononuclear cells in areas of active mucosal inflammation. For TRAIL-R1, we detected a strong downregulation in the surface epithelium in IBD but not in appendicitis. TRAIL-R2 and TRAIL-R4 were strongly downregulated in the surface epithelium in any kind of mucosal inflammation. TRAIL and TRAIL-R1 are downregulated in enterocytes, and TRAIL is upregulated in mononuclear cells only in IBD but not in normal colon or appendicitis. This may point to a pathophysiologic role of the TRAIL system in inflammatory bowel disease.